Surgical and Conservative Treatment of Post-infarction Left Ventricular Pseudoaneurysm - Zhong, Zhaoji; Song, Wu; Zheng, Shanshan; Liu, Sheng (Frontiers in Cardiovascular Medicine, 2022)
Background Post-infarction left ventricular (LV) pseudoaneurysm is a rare mechanical complication of myocardial infarction that carries a substantial risk of sudden rupture. The purpose of this study was to compare the surgical results of post-infarction LV pseudoaneurysm with those of conservative treatment. Methods From 2016 to 2021, 22 patients were hospitalized for LV pseudoaneurysm, including 17 cases (77.3%) caused by myocardial infarction. Of the 17 patients, 10 (58.8%) underwent surgical repair, while seven (41.2%) were treated medically. The clinical course, echocardiograph data, and surgical outcomes were analyzed. Survival rates of the surgical and conservative groups were compared. Results There were no perioperative deaths. Intra-aortic balloon pumping support was required in two (20%) patients. No follow-up mortality was observed in the surgical group and at the last follow-up, all the patients were classified as New York Heart Association class I–II. In the conservative group, there was one (14.3%) hospital death and two (28.6%) additional deaths during follow-up. A significant difference was found in survival between the two groups (P = 0.024). Conclusions Surgical repair of post-infarction LV pseudoaneurysm can be performed with good results, while conservative treatment carries a significant risk of sudden death. Surgical repair is indicated for every patient diagnosed, even those with a small pseudoaneurysm without symptoms.